Management of Traumatic Neck Injury with Tracheal Rupture: A Case Report - Lumintang, Nico; Megawati, Stepvani (Medical Scope Journal, 2025)
Abstract: Penetrating neck injuries are uncommon but potentially life-threatening due to the complex anatomy and the risk of airway, vascular, or esophageal compromise. Prompt diagnosis and management are critical to avoid severe complications. We presented a case of a 16-year-old male who sustained a traumatic injury to the neck due to a traffic accident. While the patient was riding a motorcycle, he hit a bridge, and his neck hit the bridge iron. The wound, located in the anterior zone II of the neck, resulted in crepitus and subcutaneous emphysema. Imaging confirmed tracheal rupture at the first and second tracheal rings. Emergency surgical exploration revealed a through-and-through tracheal injury, which was repaired with tracheostomy placement. Postoperative recovery was uneventful. The patient exhibited no signs of airway compromise, hemoptysis, or dysphagia. The emphysema resolved completely. Follow-up demonstrated a full recovery with no residual complications. In conclusion, early diagnosis and surgical management of traumatic neck injuries with tracheal involvement are vital to prevent fatal outcomes. This case highlights the importance of systematic assessment and rapid intervention in traumatic neck injuries. Surgical repair, combined with close postoperative monitoring and multidisciplinary collaboration, is essential to ensure optimal outcomes, particularly in cases involving airway trauma. Keywords: traumatic neck injury; tracheal rupture